2023
DOI: 10.1093/g3journal/jkad047
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian transcriptional response to Wolbachia infection in D. melanogaster in the context of between-genotype variation in gene expression

Abstract: Wolbachia is a maternally-transmitted endosymbiotic bacteria that infects a wide variety of arthropod and nematode hosts. The effects of Wolbachia on host biology are far-reaching and include changes in host gene expression. However, previous work on the host transcriptional response has generally been investigated in the context of a single host genotype. Thus, the relative effect of Wolbachia infection versus host genotype on gene expression is unknown. Here we explicitly test the relative roles of Wolbachia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 77 publications
(118 reference statements)
1
5
1
Order By: Relevance
“…In contrast, samples from the same type of infection shared many more patterns in TE expression, suggesting that infection type had a stronger influence on TE expression than host factors. These findings differ from other studies analyzing non-TE gene expression during infection, where host genotype had a larger effect than infection status in D. melanogaster (Frantz et al . 2023) and the type of pathogen infection in humans (Idaghdour et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, samples from the same type of infection shared many more patterns in TE expression, suggesting that infection type had a stronger influence on TE expression than host factors. These findings differ from other studies analyzing non-TE gene expression during infection, where host genotype had a larger effect than infection status in D. melanogaster (Frantz et al . 2023) and the type of pathogen infection in humans (Idaghdour et al .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding may relate to Wolbachia ’s ability to alter host gene expression that has been observed in other studies (He et al . 2019; Frantz et al . 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that Wolbachia affects many biological processes in D. melanogaster females, for which the following functional groups can be designated: "Proteolysis", "Carbohydrate transport and metabolism", "Oxidation-reduction process", "Embryogenesis", "Transmembrane transport", "Response to stress" and "Alkaline phosphatases". Earlier, transcriptome analysis in D. melanogaster infected with Wolbachia was performed using virgin and mated females [28,29], embryos [24] and in dissected ovaries [25,30] and testes [29]. No significant differences were found in the mRNA composition between Wolbachia-infected embryos and uninfected ones [24], and the effect of Wolbachia on ovaries was rather limited: only 26 DEGs were identified in two batches 2 months apart [25].…”
Section: Discussionmentioning
confidence: 99%
“…At first, we considered using only the ovaries of flies, since it is known that these organs are rich in Wolbachia. However, it had been recently demonstrated that the effects of Wolbachia on the composition of mRNA transcripts of ovaries and early embryos of D. melanogaster are limited and variable [24,25]. The data obtained allowed Frantz et al [25] to conclude that a Wolbachia infection explains only a small share of ovarian transcriptional variation compared with the variation among host lines.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation